Upaya Penanggulangan Pelanggaran Pasal 293 Ayat (2) Undang-Undang Nomor 22 Tahun 2009 Tentang Lalu Lintas Dan Angkutan Jalan - Rusmini (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2022)
Traffic is one of the means of community communication that plays an important role in facilitating the implementation of national development. There are three main components of traffic, namely humans as users, vehicles and roads that interact with each other in the movement of vehicles that meet the eligibility requirements to be driven by the driver following the traffic rules established based on laws and regulations concerning traffic and road transportation through roads that meet geometric requirements. . What are the efforts to overcome violations of Article 293 Paragraph (2) of Law Number 22 Year 2009 concerning Road Traffic and Transportation. Normative legal research or doctrinal research, namely research conducted or intended to examine the content of written regulations or other legal materials. The factor of violation of Article 293 Paragraph (2) of Law Number 22 Year 2009 concerning Road Traffic and Transportation. Efforts to overcome violations of Article 293 Paragraph (2) of Law Number 22 Year 2009 concerning Road Traffic and Transportation. It is necessary to carry out comprehensive and comprehensive socialization activities through various media by prioritizing the rationality and urgency of the importance of the rule of law. The need to increase awareness for the public to follow and carry out every regulation contained in Law No. 22 of 2009 concerning Road Traffic and Transportation for the smooth flow of traffic and the safety of motorists. The Traffic Police are expected to further improve their performance in dealing with traffic violations and to pay more attention to the quality and quantity of Traffic Police officers so that in dealing with traffic violations they do not encounter obstacles and run as expected